An action research on creating standard workflow for partnership group division in a Philippine based NGO - Importante, Marlyn G. (Animo Repository, 2016)
This action research aims to address the variability on the workflow of partnership management process. For the work routine who manages multiple partners like Partnership Manager worked within Partnership Group, it is paramount to follow a standard workflow to avoid variability and inconsistencies in delivering of partnership management process. This issue has been a hindrance in GKCFI, a Philippine based NGO in delivering efficient service. To address the focal issue of having lack of documented standard workflow, the agreed objectives are the following: (i) to create standard partnership management workflow, (ii) to introduce the concept of Kaizen PDCA tool in improving standard processes, and (iii) to implement continuous improvement in handling Corporate Social Responsibility inquiries. The agreed interventions to address the issue were the following: (i) first cycle- to create a written partnership management workflow and (ii) second cycle improve the CSR inquiries workflow. To achieve this goal, I, the researcher, and my collaborators used the Kaizen- PDCA Cycle in analyzing the issue into a more systematic way and the Kurt Lewin Change Management model to manage the resistance of employees towards change. Both cycles were successful based on actual outcomes. The use of the PDCA Cycle helped us identify the root cause of the issue and plan the implemented interventions. This research also helped improved the teamwork and communication within the Partnership Group and achieved work efficiency by eliminating the variability of processes. In doing this action research, I have improved my collaborative skills within and across other departments. Moreover, I realized if we know how to listen, we can build a healthier working relationship.